Simulation of classical skiing using a new ski tester - Linnamo, V.; Kolehmainen, V.; Vähäsöyrinki, P.; Komi, P. (Science and Skiing IV, 2008)
INTRODUCTION: Force production plays an important role in classical cross-country skiing. By using a special force plate System it is possible to measure both vertical and horizontal forces during diagonal skiing (e.g Komi & Norman 1987). The effects of waxing and ski properties are, however, difficult to estimate accurately as the force production even in experienced skier may vary considerably. The purpose of the present study was to construct a novel ski tester that would simulate the force production of natural skiing and allow accurate measurements in laboratory conditions.